Essential role of Mohawk for tenogenic tissue homeostasis including spinal disc and periodontal ligament. Issue 6 (2nd November 2018) - Nakamichi, Ryo; Kataoka, Kensuke; Asahara, Hiroshi
Abstract: Tendons and ligaments play essential roles in connecting muscle and bone and stabilizing the connections between bones. The damage to tendons and ligaments caused by aging, injury, and arthritis induces the dysfunction of the musculoskeletal system and reduces the quality of life. Current therapy for damaged tendons and ligaments depends on self-repair; however, it is difficult to reconstruct normal tissue. Regeneration therapy for tendons and ligaments has not been achieved, partly because the mechanism, cell biology, and pathophysiology of tendon and ligament development remain unclear. This review summarizes the role of the transcription factor, Mohawk, which controls tendon and ligament cell differentiation, in the maintenance of cell homeostasis, as well as its function in disease and the possibility of new therapeutic approaches.